Cardioprotection by H2S engages a cGMP-dependent protein kinase G/phospholamban pathway - Bibli, S. I.; Andreadou, I.; Chatzianastasiou, A.; Tzimas, C.; Sanoudou, D.; Kranias, E.; Brouckaert, P.; Coletta, C; Szabo, C.; Kremastinos, D.T.; Iliodromitis, E.K.; Papapetropoulos, A. (Cardiovasc ResCardiovasc ResCardiovasc Res, 2015)
AIMS: H2S is known to confer cardioprotection; however, the pathways mediating its effects in vivo remain incompletely understood. The purpose of the present study is to evaluate the contribution of cGMP-regulated pathways in the infarct-limiting effect of H2S in vivo. METHODS AND RESULTS: Anaesthetized rabbits were subjected to myocardial ischaemia (I)/reperfusion (R), and infarct size was determined in control or H2S-exposed groups. The H2S donor sodium hydrosulfide (NaHS, an agent that generates H2S) increased cardiac cGMP and reduced the infarct size. The cGMP-dependent protein kinase (PKG)-I inhibitor DT2 abrogated the protective effect of NaHS, whereas the control peptide TAT or l-nitroarginine methyl ester (l-NAME) did not alter the effect of NaHS. Moreover, the KATP channel inhibitor, glibenclamide, partially reversed the effects of NaHS, whereas inhibition of mitochondrial KATP did not modify the NaHS response. NaHS enhanced phosphorylation of phospholamban (PLN), in a PKG-dependent manner. To further investigate the role of PLN in H2S-mediated cardioprotection, wild-type and PLN KO mice underwent I/R. NaHS did not exert cardioprotection in PLN KO mice. Unlike what was observed in rabbits, genetic or pharmacological inhibition of eNOS abolished the infarct-limiting effect of NaHS in mice. CONCLUSIONS: Our findings demonstrate (i) that administration of NaHS induces cardioprotection via a cGMP/PKG/PLN pathway and (ii) contribution of nitric oxide to the H2S response is species-specific.
Bibli, Sofia-IrisAndreadou, IoannaChatzianastasiou, AthanasiaTzimas, ChristosSanoudou, DespinaKranias, EvangeliaBrouckaert, PeterColetta, CiroSzabo, CsabaKremastinos, Dimitrios ThIliodromitis, Efstathios KPapapetropoulos, AndreasengR01 GM107846/GM/NIGMS NIH HHS/R01 HL026057/HL/NHLBI NIH HHS/R01 HL064018/HL/NHLBI NIH HHS/Research Support, N.I.H., ExtramuralResearch Support, Non-U.S. Gov'tEngland2015/04/15 06:00Cardiovasc Res. 2015 Jun 1;106(3):432-42. doi: 10.1093/cvr/cvv129. Epub 2015 Apr 13.
Keywords: Animals; Calcium-Binding Proteins/deficiency/genetics/*metabolism; Cyclic GMP-Dependent Protein Kinases/antagonists & inhibitors/*metabolism; Cyclic GMP/metabolism; Disease Models, Animal; Enzyme Activation; Female; Hydrogen Sulfide/metabolism/*pharmacology; Male; Mice, Inbred C57BL; Mice, Knockout; Myocardial Infarction/enzymology/pathology/*prevention & control; Myocardial Reperfusion Injury/enzymology/pathology/*prevention & control; Myocytes, Cardiac/*drug effects/enzymology/pathology; Nitric Oxide Synthase Type III/antagonists & inhibitors/genetics/metabolism; Nitric Oxide/metabolism; Phosphorylation; Protein Kinase Inhibitors/pharmacology; Rabbits; Signal Transduction/*drug effects; Species Specificity; Sulfides/metabolism/*pharmacology